The Application of Strategic Human Resource Practice Based on Tri Kaya Parisudha to Improve The Performance of Village Financial Institution Employees in Buleleng Regency - Yudi Prastiwi, Ni Luh Putu Eka; Ningsih, Luh Kartika; Rianita, Ni Made (Universitas Pendidikan Ganesha, 2018)
The purpose of this study was to determine the effect of Skill Employment based Tri Kaya Parisudha, Affective Commitment, Reward Management toward the Employee Performance. This research was explanatory with the form of causality between variables. The number of samples in this study were 51 respondents selected based on the Stratified Random Sampling method. The data analysis technique used in this study was the structural equation model (Structural Equation Modeling-SEM) based on variance or Component based SEM with the SmartPLS 3.0 analysis tool. The conclusion of this study was Strategic Human Resource Practice based Tri Kaya Parisudha can be applied in the Village Financial Institution Buleleng Regency to improve the Employee Performance of Village Financial Institution in Buleleng Regency